The effect of tax planning activities and firm characteristic: Evidence from Indonesia - Kennardi Tanujaya; Winda Lius (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2023)
This study's purpose of contributing to the literature by empirically examining the effect of tax planning, activities, financial debt, audit quality, and firm investment on the firm value. This study adopts quantitative method research using panel regression with 1,264 data samples for model 1 and 1,291 data samples for model 2 with observation year from 2017-2021. This study shows that audit quality and tax planning have a significant positive impact on firm value. In contrast to firm investment, financial debt has a significant negative effect on firm value, which has insignificant results. This research contribution is that companies should pay attention to the selection of auditors for a financial audit because the auditor's role has a positive impact on the firm value. Also, investors can see the value of companies eligible for investment considering the tax planning activities in advance of the company carried out. The novelty of this research is the use of measurement of tax per share for tax planning, rarely used by the other researcher in conducting a relationship between firm value and tax planning. Public interest statement This study is necessary because the auditor's role is critical in minimizing the profit-making practices of managers and ensuring the quality of corporate earnings reporting. Investors can also pay attention to the value of a company worth investing in by paying attention to the tax planning activities undertaken by a company. Article history Received 26 Nov 2022 | Revised 10 Jan 2023 | Accepted 11 Jan 2023 | Online First 03 Feb 2023